Security Operation Center Based on Immune System - Yi Niu; Quanju Zhang; QiLun Zheng; Hong Peng (CIS Workshops 2007 : 2007 International Conference on Computational Intelligence and Security Workshops : proceedings : 15-19 December, 2007, Harbin, Heilongjiang, China, 2007)
With the widespread application of large and complicated network, network safety has become an important issue. In this paper, we design a security operation center (SOC) using an analogy of natural world immunology, We adopt an immune mechanism that distinguishes self from non-self and cooperation among immune cells of the system. This system implements each immune cell as an agent based on our multi-agent language, which his an extension of concurrent logic programming languages. These agents can detect and reject intrusion by cooperating with each other.